IMPLEMENTASI PELAYANAN PUBLIK BERBASIS TEKNOLOGI INFORMASI (STUDI KASUS DI BADAN PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL KOTA BOGOR) - Febryan, Denise; Erviantono, Tedi; Winaya, I Ketut (CITIZEN CHARTER, 2016)
ABSTRACT The implementation of public services based on information technology in Bogor City Licensing Agency aimed to see if the problems that exist in licensing services to be better or not using technology equipment. This research was conducted also to look at the benefits and obstacles to their implementation of information technology in the public service based on information technology. To look at a complex problem and requires in-depth understanding, this research method using descriptive qualitative. For the result of that, it is necessary to do the interview, observation and documentation study to be able to get valid data. This research was held in the Integrated Licensing Services and Investment Coordinating Board in the city of Bogor. Based on the results of this study concluded that the quality of public services based on information technology has been dissatisfactory. The indicators of public policy implementation are seen through communication, resources, dispotition and bureaucratic structure with the consideration of transparency, participation and efficiency aspect. Public services based on information technology has not been able to provide accurate information for the public, community participation has not been good and the employees of Integrated Licensing Services and Investment Coordinating Board in the city of Bogor are lack utilizing the existing technology. The public services that is fast, easy, and appropriate in the presence of information technology has not been implemented due to the lack of use on online systems in the community. Keywords : Policy implementation, Public Services, Information Technology, Integrated Licensing Services and Investment Coordinating Board in the city of Bogor